(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
Background: The skin is the body’s first physical line of defense, functioning to protect against dehydration and to prevent the entry of harmful foreign agents, such as bacteria. Mango leaves (Mangifera indica L.) possess antibacterial properties due to the presence of tannins, alkaloids, saponins, flavonoids, and mangiferin. Mangiferin belongs to the xanthone and phenolic compound groups and has potential antimicrobial activity. Objective: This community service activity aimed to improve community knowledge and skills in producing antibacterial liquid soap made from mango leaf (Mangifera indica L.) extract, as well as to encourage the implementation of clean and healthy living behaviors. Methods: The delivery of community service materials was carried out using a lecture method supported by infocus media. The preparation of liquid soap containing mango leaf extract was conducted through demonstration and hands-on practice by the participants. Results: The community service activity resulted in a liquid soap product with a pH ranging from 8 to 11, a characteristic mango leaf aroma, and a foam height of approximately 1–5 cm, which meets the Indonesian National Standard (SNI) for soap (1996), namely 0–5 cm. Posttest evaluation showed that 86.7% (26 participants) had a good level of knowledge, while 13.3% (4 participants) had a moderate level of knowledge. Conclusion: This community service activity indicates that the participants understood the material provided and were able to effectively demonstrate the production of antibacterial liquid soap made from mango leaf extract.